Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Inspektorat Kabupaten Tapanuli Tengah - Ratna Widha Simanjuntak; Mansur Tanjung; Mhd. Shafwan Koto (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to determine the effect of work discipline and work environment on employee performance at the Inspectorate Office of Central Tapanuli Regency. This research uses a quantitative method with a descriptive approach. The sample consisted of 37 respondents who are employees of the Inspectorate Office of Central Tapanuli Regency, and data were collected through questionnaires. The results show that the coefficient of determination (R²) is 0.760, indicating that 76% of the variation in employee performance can be explained by work discipline and work environment simultaneously, while the remaining 24% is influenced by other variables not examined in this study. The partial test (t-test) results indicate that work discipline has a positive and significant effect on employee performance (t-count 3.361 > t-table 2.032; sig 0.002 < 0.05), and the work environment also has a positive and significant effect on employee performance (t-count 6.726 > t-table 2.032; sig 0.001 < 0.05). Furthermore, the simultaneous test (F-test) shows that work discipline and work environment together have a positive and significant effect on employee performance (F-count 53.876 > F-table 3.25; sig 0.001 < 0.05). Therefore, it can be concluded that work discipline and work environment are important factors in improving employee performance at the Inspectorate Office of Central Tapanuli Regency.